A transitional approach to the study of the information behavior of domestic migrant workers: A narrative inquiry. Issue 2 (6th March 2019) - Bronstein, Jenny
Abstract : Purpose: The purpose of this paper is to examine the life stories of migrant workers in Israel by analyzing different aspects of the information behavior that emerged from their narratives through a transitional perspective. Design/methodology/approach: Narratives are a human way of communication that focuses on the stories people tell about themselves, their inner thoughts, their states of mind and how they perceive their own reality. In total, 20 Spanish-speaking domestic migrant workers were interviewed. The data collected form the narratives were study draws from the transitional theory. Findings: The holistic phase of the content analysis revealed that participants experienced information poverty based on socioeconomic factors and perceptions of social exclusion, vulnerability and hostile surroundings. The content analysis yielded a theory of transitional information behavior that reflects the three stages of the migration process: ending of a new reality, a period of confusion and a sense of belonging. The theory encompasses four elements: process, disconnectedness, perceptions and patterns of response. Originality/value: The study proposes an innovative look at information behavior of migrants by integrating a transitional perspective into the life stories of participants.